2017
DOI: 10.1371/journal.pone.0174166
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated plasma levels of cardiac troponin-I predict left ventricular systolic dysfunction in patients with myotonic dystrophy type 1: A multicentre cohort follow-up study

Abstract: ObjectiveHigh sensitivity plasma cardiac troponin-I (cTnI) is emerging as a strong predictor of cardiac events in a variety of settings. We have explored its utility in patients with myotonic dystrophy type 1 (DM1).Methods117 patients with DM1 were recruited from routine outpatient clinics across three health boards. A single measurement of cTnI was made using the ARCHITECT STAT Troponin I assay. Demographic, ECG, echocardiographic and other clinical data were obtained from electronic medical records. Follow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…On multivariable analysis, NT‐proBNP and CP were independently associated with incident paroxysmal AF in DM1 population. Increased levels of cardiac‐specific serum biomarkers in DM1 patients compared with controls have been previously reported . In a recent case‐control study, Valperta et al suggested that the hs‐cTnT might represent a helpful serum biomarker to predict cardiac risk in DM disease, below our ability to detect it with conventional measures.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On multivariable analysis, NT‐proBNP and CP were independently associated with incident paroxysmal AF in DM1 population. Increased levels of cardiac‐specific serum biomarkers in DM1 patients compared with controls have been previously reported . In a recent case‐control study, Valperta et al suggested that the hs‐cTnT might represent a helpful serum biomarker to predict cardiac risk in DM disease, below our ability to detect it with conventional measures.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent case‐control study, Valperta et al suggested that the hs‐cTnT might represent a helpful serum biomarker to predict cardiac risk in DM disease, below our ability to detect it with conventional measures. More recently, Hamilton et al in a multicenter study including 117 DM1 patients followed for a mean of 23 months demonstrated that elevated serum hs‐cTnI levels were associated with left ventricular systolic dysfunction, but did not correlate with advanced conducting system disease on surface ECG. These findings suggest that high sensibility troponins might be a useful tool to aid risk stratification in DM1 patients, adding value to surface ECG in identifying those at increased risk of cardiovascular disease or those with manifest cardiac muscle involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac involvement is an important cause of premature death in DM patients and one possible molecular explanation to cardiac dysfunctions is the misregulation of alternative splicing of TNNT2 and SCN5A pre-mRNA in cardiac tissue (25, 26). Recently, several authors have reported that DM patients show elevated serum levels of cTnT, cTnI, and NT-pro-BNP, suggesting that these serum cardiac biomarkers could be used to identify DM patients at increased risk of developing myocardial conduction abnormalities and for stratification of subjects in clinical trials (34, 43, 46). However, to date, no cardiac biomarkers have been identified that may serve as an accurate biomarker of cardiac involvement that could be used in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“… 22–24 hs-cTnI levels in DM type I were highly elevated in ambulatory subjects and predictive of cardiac dysfunction (Architect Stat Troponin Assay, Abbott). 25 Elevated cTnI levels were observed in patients with Friedreich’s ataxia. 26 Elevated troponin levels also occur in patients with spinal muscular atrophy (SMA), and transient increases in cTnI levels (up to 0.176 µg/L; assay and normal limit not reported) of unclear significance were observed following Zolgensma infusion in clinical trials.…”
Section: Troponin and Neuromuscular Diseasesmentioning
confidence: 99%